PENGATURAN PENGELOLAAN KONSERVASI KELAUTAN BERKELANJUTAN - Gatot Dwi Hendro Wibowo (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
As archipelago state, Indonesia has biggest biological diversity of marine in the world. It needs a good manage and consider with the needs of present without compromising the ability of future generations to meet their own needs. The most important to realize this objective is a make regulation related with marine and coastal resources of law. The regulation must be consider with sustainable development principle especially precautionary principle and conservation on biological diversity principle.